Mechanoluminescence: Mechanically Excited Multicolor Luminescence in Lanthanide Ions (Adv. Mater. 7/2019). Issue 7 (12th February 2019) - Du, Yangyang; Jiang, Yue; Sun, Tianying; Zhao, Jianxiong; Huang, Bolong; Peng, Dengfeng; Wang, Feng
Abstract : Mechanoluminescent materials that convert mechanical stimuli ubiquitously available in nature into light emissions find enormous applications in sensing, information, and energy technology. In article number1807062, Bolong Huang, Dengfeng Peng, Feng Wang, and co‐workers develop a class of lanthanide‐doped CaZnOS mechanoluminescent crystals. They demonstrate unprecedented multicolor tuning of mechanoluminescence in the full spectrum, spanning violet to the near infrared.